Effectiveness of coal mine dust control: A new technique for preparation and efficacy of self-adaptive microcapsule suppressant - Ren, Bo; Yuan, Liang; Zhou, Gang; Li, Shuailong; Meng, Qunzhi; Wang, Kai; Jiang, Bingyou; Yu, Guofeng (International journal of mining science and technology, 2022)
[Display omitted] This study aims to make full use of the agricultural waste peanut shells to lower material costs and achieve cleaner production at the same time. Cellulose nanofibrils (CNF) extracted from peanut shells were mixed with acrylic acid (AA) and dimethyl diallyl ammonium chloride (DMDAAC) to prepare a new type of capsule core (dust suppressant). Then, the self-adaptive AA-DM-CNF/CA microcapsules were prepared under the action of calcium alginate. The infrared spectroscopy and X-ray diffraction analysis results suggest that AA, DMDAAC and CNF have experienced graft copolymerization which leads to the formation of an amorphous structure. The scanning electron microscopy analysis results demonstrate that the internal dust suppressant can expand and break the wall after absorbing water, featuring a self-adaptive function. Meanwhile, the laser particle size analysis results show that the microcapsules, inside which the encapsulated dust suppressant can be observed clearly, maintain a good shape. The product performance experimental results reveal that the capsule core and the capsule wall achieve synergistic dust suppression, thus lengthening the dust suppression time. The product boasts good dust suppression, weather resistance, degradation and synergistic combustion performances. Moreover, this study, as the first report on the development and analysis of dust-suppressing microcapsules, fills in the research gap on the reaction mechanism between dust-suppressing microcapsules and coal by MS simulation. The proposed AA-DM-CNF/CA dust-suppressing microcapsules can effectively lower the dust concentration in the space and protect the physical and mental health of coal workers. In general, this research provides a new insight into the structure control and performance enhancement of dust suppressants. Expanding the application range of microcapsules is of crucial economic and social benefits.